Association Between Night-Shift Work and Cancer Risk: Updated Systematic Review and Meta-Analysis - Dun, Aishe; Zhao, Xuan; Jin, Xu; Wei, Tao; Gao, Xiang; Wang, Youxin; Hou, Haifeng (Frontiers in Oncology, 2020)
Abstract Background: Nightshift work introduces light at night and causes circadian rhythm among night workers, who are considered to be at increased risk of cancer. However, in the last two years, nine population-based studies reported insignificant associations between night-shift work and cancer risks. We aimed to conduct an updated systematic review and meta-analysis to ascertain the effect of night-shift work on the incidence of cancers. Methods: Our protocol was registered in PROSPERO and complied with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Embase, PubMed and Web of Science databases were used to comprehensively search studies published up to May 31, 2019. The random-effect model (Der Simonian-Laird method) was carried out to combine the risk estimates of night-shift work for cancers. The dose-response meta-analysis was performed to verify whether the association was in a dose-dependent manner. Results: Our literature searching retrieved 1,660 publications. Included in the meta-analyses were 57 eligible studies with 8,477,849 participants (mean age 55 years; 2,560,886 men, 4,220,154 women and 1,696,809 not mentioned). The pooled results showed that night-shift work was not associated with the risk of breast cancer (OR= 1.009, 95% CI=0.984-1.033), prostate cancer (OR=1.027, 95% CI=0.982-1.071), ovarian cancer (OR=1.027, 95% CI=0.942-1.113), pancreatic cancer (OR=1.007, 95% CI=0.910-1.104), colorectal cancer (OR=1.016, 95% CI=0.964-1.068), non-Hodgkin’s lymph (OR=1.046, 95% CI=0.994-1.098), and stomach cancer (OR=1.064, 95% CI=0.971-1.157), while night-shift work was associated with a reduction of lung cancer (OR=0.949, 95% CI=0.903-0.996), and skin cancer (OR=0.916, 95% CI=0.879-0.953). The dose-response meta-analysis found that cancer risk was not significantly elevated with the increased light exposure of night- shift work. Conclusion: This systematic review of 57 observational studies did not find an overall association between ever-exposure to night-shift work and the risk of breast, prostate ovarian, pancreatic, colorectal, Non-Hodgkin’s lymph, and stomach cancers.